2006
DOI: 10.1001/archinte.166.2.213
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Erectile Dysfunction in the Primary Care Setting

Abstract: Cardiovascular disease, diabetes, future coronary risk, and increasing fasting glucose levels are independently associated with ED. It remains to be determined if ED precedes the development of these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(57 citation statements)
references
References 35 publications
1
44
1
2
Order By: Relevance
“…This association between erectile dysfunction and cardiovascular risk is complex as erectile dysfunction commonly coexists with conditions that are associated with increased risk of cardiovascular disease, namely obesity, metabolic syndrome and Type II diabetes, which are also associated with lower testosterone levels. 80,81,97,99 Thus, lower testosterone levels are associated with higher body mass index (BMI), and with increased prevalence and incidence of metabolic syndrome and Type II diabetes in middle-aged and older men. 10,11,13,14,19,[100][101][102][103][104][105][106][107] In addition, lower testosterone levels are associated with surrogate markers for cardiovascular disease, including less favorable carotid intima medial thickness, 108-110 ankle/brachial index as a measure of peripheral arterial disease 111 and calcific aortic atheroma.…”
Section: Testosterone Cardiovascular Risk and Mortality In Aging Menmentioning
confidence: 99%
“…This association between erectile dysfunction and cardiovascular risk is complex as erectile dysfunction commonly coexists with conditions that are associated with increased risk of cardiovascular disease, namely obesity, metabolic syndrome and Type II diabetes, which are also associated with lower testosterone levels. 80,81,97,99 Thus, lower testosterone levels are associated with higher body mass index (BMI), and with increased prevalence and incidence of metabolic syndrome and Type II diabetes in middle-aged and older men. 10,11,13,14,19,[100][101][102][103][104][105][106][107] In addition, lower testosterone levels are associated with surrogate markers for cardiovascular disease, including less favorable carotid intima medial thickness, 108-110 ankle/brachial index as a measure of peripheral arterial disease 111 and calcific aortic atheroma.…”
Section: Testosterone Cardiovascular Risk and Mortality In Aging Menmentioning
confidence: 99%
“…4,5 A prevalence of 35% ED was found in a study as early as 1980 in patients with diabetes mellitus. 1 The prevalence of ED was found to be 49% in men aged 40-88 years in a Canadian study, 6 while severe ED was found in 30% of men in a large study in Israel. 7 A prevalence of ED of as high as 71% was also demonstrated in another study in France.…”
Section: Introductionmentioning
confidence: 97%
“…9 Multiple modifiable risk factors were found to be independently associated with ED in several trials, including diabetes mellitus, obesity, current smoking and hypertension. 5,6 The prevalence of ED increased progressively with age. Other important associations were treatment with insulin or oral hypoglycaemic agents, retinopathy, and symptomatic autonomic and peripheral neuropathy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations